PERLINDUNGAN KONSUMEN ATAS PRODUK CACAT DAN GAGAL - Joel Antonio Freitas; Ruli vita sari; Aris Prio Agus Santoso (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
In modern developments or what could be called the digital era, many sellers use digital media to buy and sell their goods easily and consumers will be more interested in this method of selling. Consumers do not need to leave the house, but consumers are often harmed by defective and failed products circulating on the market. This creates a violation of consumer rights and can endanger their safety. The aim of this research is to determine legal protection for consumers for defective and failed products in Indonesia. This research uses normative juridical methods with a legal approach, literature studies and other secondary data. Law Number 8 of 1999 concerning Consumer Protection provides legal protection for consumers for defective and failed products. The research results are then explained qualitatively. Based on the research results, it shows that the form of consumer protection for consumers is compensation for losses, product replacement, or a refund if they buy a defective and failed product. This research also found several obstacles in enforcing consumer protection laws, such as lack of consumer awareness, weak law enforcement, and minimal information available for Consumer legal protection against defective and failed products in Indonesia still needs to be strengthened. Efforts need to be made to increase consumer awareness, strengthen law enforcement, and increase access to information for consumers.